1982
DOI: 10.23818/actas.01.04
|View full text |Cite
|
Sign up to set email alerts
|

Indicadores ecológicos de algunos ecosistemas acuáticos del Bajo Guadalquivir (SW; España): odonatos heterópteros y coleópteros acuáticos

Abstract: ECOLOGICAL INDICATORS OF SOME AQUATIC ECOSYSTEMS OF "BAJO GUADALQUIVIR" (S.W. SPAIN): ODONATA AND AQUATIC HETEROPTERA ANO COLEOPTERA Toe indicator value of 56 populations of Odonata and aquatic Coleoptera and Heteroptera was detennined from aquatic ecosystems of low Guadalquivir river by a statistical procedure (Binary Discriminant Analysis), as a part of a general ecological study.In general, permanent sites on sand substrate are used as temporary residences by a great number of migratory species of Coleopter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

1991
1991
1991
1991

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
0
0
Order By: Relevance
“…Previous physical and chemical data (Montes et al, 1982;Furest & Toja, 1981) indicated a progressive increase in calcium and pH values. Changes in phytoplanktonic communities can also be observed: the dominant species are different from those quoted by other researchers (Margalef, 1976); and Spirulina platensis, a species typical of alkaline waters (Margalef, 1983), not mentioned before, now appears among the phytoplankton.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Previous physical and chemical data (Montes et al, 1982;Furest & Toja, 1981) indicated a progressive increase in calcium and pH values. Changes in phytoplanktonic communities can also be observed: the dominant species are different from those quoted by other researchers (Margalef, 1976); and Spirulina platensis, a species typical of alkaline waters (Margalef, 1983), not mentioned before, now appears among the phytoplankton.…”
Section: Discussionmentioning
confidence: 88%
“…From a limnological point of view, there have been previous studies on water chemistry (Margalef, 1976;Furest 8c Toja, 1981Montes et al, 1982), phytoand zooplankton (Bigot 8c Marazanoff, 1965;Margalef, 1976;Armengol, 1976;Furest 8c Toja, 1984, 1987, which showed differences be tween the two ponds in spite of their proximity. Nevertheless these studies, being sporadic and short-termed, have not allowed us to understand how long term fluctuations affect the limnological features of both ponds.…”
Section: Introductionmentioning
confidence: 98%